2013
DOI: 10.1111/1755-0998.12081
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution melting analysis for bird sexing: a successful approach to molecular sex identification using different biological samples

Abstract: High-resolution melting (HRM) analysis is a very attractive and flexible advanced post-PCR method with high sensitivity/specificity for simple, fast and cost-effective genotyping based on the detection of specific melting profiles of PCR products. Next generation real-time PCR systems, along with improved saturating DNA-binding dyes, enable the direct acquisition of HRM data after quantitative PCR. Melting behaviour is particularly influenced by the length, nucleotide sequence and GC content of the amplicons. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Therefore, for accurate sex identification in these species alternative gametologs such as NIPBL or alternative CHD1 based primers might be used (Suh et al, ). It has recently been shown that high resolution melting curve (HRM) real time PCR and oligonucleotide microarrays may be useful for accurate sex identification in Strigidae (Morinha et al, ; Wang et al, ). P2/P3 is another CHD1 ‐specific primer that has been used for sex identification in birds of prey.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for accurate sex identification in these species alternative gametologs such as NIPBL or alternative CHD1 based primers might be used (Suh et al, ). It has recently been shown that high resolution melting curve (HRM) real time PCR and oligonucleotide microarrays may be useful for accurate sex identification in Strigidae (Morinha et al, ; Wang et al, ). P2/P3 is another CHD1 ‐specific primer that has been used for sex identification in birds of prey.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of consumer DNA, a variety of methods for sex determination ("molecular sexing") and individual identification have been developed (e.g., Kohn & Wayne, 1997;Wultsch, Waits, & Kelly, 2014). For birds, molecular sexing has been commonly applied since the late 1990s to determine the sex of indistinguishable adult birds, juveniles, and embryos (Morinha et al, 2013). Generally, the technique is based on sequence variations of the sex chromosomes, and depending on the species under investigation, different primers have been developed and applied in allele-specific PCRs (Dawson, Dos Remedios, & Horsburgh, 2016;Morinha, Cabral, & Bastos, 2012).…”
Section: The Great Variety Of Freshwater Habitats In the Central Euromentioning
confidence: 99%
“…For European cormorants, Thanou, Giokas, Goutner, Liordos, and Fraguedakis-Tsolis (2013) found the primers 2550F and 2718R (Fridolfsson & Ellegren, 1999), targeting the chromodomain-helicase-DNA-binding protein 1 gene (CHD1) to be best suited for molecular sexing. Traditionally, blood, feathers, muscle tissue, egg shells, and buccal swab samples have been used as a source of bird DNA (Griffiths, Daan, & Dijkstra, 1996;Morinha et al, 2013;Thanou et al, 2013), but recently, molecular sexing has also been successfully carried out with fecal samples (e.g., Faux, McInnes, & Jarman, 2014;Jarman et al, 2013).…”
Section: The Great Variety Of Freshwater Habitats In the Central Euromentioning
confidence: 99%
“…This requires the transport of samples and usually implies that sex determination may take several days after collecting the samples. Although high‐resolution melting analysis is an accurate technique for sex determination in birds (Faux, McInnes, & Jarman, ; Morinha et al., ), hand‐held devices for quantitative PCRs required for a portable solution are still expensive and made these protocols unaffordable for most laboratories. Loop‐mediated isothermal amplification (LAMP; Notomi, Mori, Tomita, & Kanda, ; Notomi et al., ) can lift these constraints on time, space and resources.…”
Section: Introductionmentioning
confidence: 99%